Compliance with Covid -19 health measures in adolescents: The role of personal fable, sensation seeking and social alienation - Naeimijoo, Parastoo; Yousefi , Ahmad; Masjedi Arani , Abbas; Bazani, Meysam; Khadem, Hosein (Researcher Bulletin of Medical Sciences, 2023)
Background and Objective: The COVID-19 emergence obliged many governments to exert public health measures. However, it seems a vast difference in levels of respect towards health-related guidelines. Among all age groups, adolescents are known to have low conformity to such rules and display a crucial role in spreading the virus. In efforts trying to find the key contributing factors of such extensive non-compliance, much pandemic research attention has been focused on the adult population and adolescents have not been widely addressed. This paper examined the role of personal fable, sensation seeking and social alienation in the adoption of Covid-19 recommended practices in adolescents. Materials and Methods: This cross-sectional study collected data from 355 adolescents during strict restrictions imposed on the country. The survey was administered online over three weeks. Participants were asked to complete self-report measures. Data were analyzed by correlation and regression analysis. Results: Data shows an inverse correlation between the variables and compliance, among which disinhibition and invulnerability had the strongest association. These subscales were predictors of non-conformity with official pandemic guidelines. Likewise, social alienation was predictive of rule disrespect. Furthermore, females and those lacking history of Corona disease exhibited more active pandemic-related behaviors. Conclusions: It seems that some peculiar characteristics of this developmental stage have an outstanding role in explaining adherence to pandemic-related preventative behaviors.